Beta-i : analyzing the gap between brand identity and brand image - Pina, Ana Maria Filipe (2018)
Enterprises are constantly challenged by the changing environment and market conditions. Brands are a key resource that companies possess to differentiate themselves from competitors. In order to assure effective branding strategies are being implemented, there is a need to evaluate the gap between Brand Image and Brand Identity. Up to now, no relevant research has been conducted within the field of branding regarding accelerators. To fill in this field gap the example of the Portuguese company Beta-i was used. Therefore, a study was conducted regarding four brand dimensions: Vision and Culture, Positioning, Personality and Relationship and within two groups of stakeholders: startups and corporations. The data was collected via online survey and consisted of 75 responses divided by the two groups. The analysis suggests that there exists a gap between Brand Image and Brand Identity when it comes to the perceptions regarding Positioning and Relationship. Additionally, results seem to show that both stakeholder groups have different perceptions of the same Brand Identity. This findings try to illutratre the existing gaps that exist in branding stratagies which should be address by corporations since they could potencially leed to negative and misleading perceptions towards their brand. Due to the inadequate reliability of the study future research needs to improve this research by gathering a larger sample.